Community Attitudes Toward Local Foods and Producers: The Role of Warmth Versus Competence Across Demographics for Social Media Engagement. - Danielle L Eiseman; Andrea Stevenson Won (Journal of Applied Communications, 2023)
Connecting local food producers with consumers is useful for ensuring individuals have access to healthy, fresh, foods. Small farmers, however, lack the resources to effectively connecting with consumers through traditional forms of marketing. Marketing to consumers through social media is a low-cost method that local food producers can use to promote their products. Creating engaging content on social media can be challenging, thus there is a need for guidance on how to effectively engage with local consumers through social media. Studies in advertising have shown dimensions of warmth and competence can be useful frames for engaging consumers across a variety of consumer goods. In this study we ran a nationally representative survey (n = 966) with an experimental component to determine if videos were an effective method of connecting with consumers, and if so, how this varies across demographics. We further investigated whether aspects of warmth of competence influence consumer willingness to purchase locally produced foods. We find warmth does have a small effect on consumer perceptions of local foods and videos help reduce the lack of familiarity of a farm, a barrier to purchasing local foods. Consumers across demographics demonstrate high levels of interest in purchasing local foods yet access to continues to be a barrier to purchasing. Additionally, we find consumers are willing to purchase locally produced foods at a higher price if available in more convenient locations, such as grocery stores, provided they were clearly labeled and from a farm that is familiar.
Keywords: Attitudes; perceptions; local food; farmers; social media